Altered-function mutations of the transcriptional regulatory gene virG of Agrobacterium tumefaciens. - Han, D C (1992)
Three point mutations were isolated in the Agrobacterium tumefaciens virG gene by screening for vir gene expression in the absence of added phenolic inducing compounds. All three mutations were localized in the predicted amino-terminal phosphoryl receiver domain of the protein. One mutant (N54D) bypasses the requirement for VirA and phenolic inducers both for transcriptional activation of all tested vir promoters and for plant tumorigenesis. This mutant also activates vir gene expression efficiently at neutral pH, indicating that the step in induction that is normally stimulated by acid pH occurs before or during VirG phosphorylation. The other two mutants (M13T and H15R) require VirA for activity but are sensitized to low levels of inducing stimuli.